Language and Ambiguity: A Study on Unclear Titles in Linguistic Studies - Mohamed Ibrahim Hassan Othman; Mohamed Aziz Abdelmaksoud Sayed Ahmed; Ummu-Hani Binti Abas; Mohamad Zhafri Mohammad Nazmi; Abdel Sattar Abd Elwahab Ayoub Othman (HRMAS, 2025)
Indexed by ERA (Tier 2)